1997
DOI: 10.2172/565626
|View full text |Cite
|
Sign up to set email alerts
|

DOSFAC2 user`s guide

Abstract: iil

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Over the years, studies conducted on the modus operandi of sexual offenders against children showed that these offenders exhibit some rationality in that they adopt strategies along a temporal continuum (e.g. to gain trust, to gain cooperation and to maintain victims' silence following the onset of abuse) to commit their crimes (e.g., Elliott, Browne, & Kilcoyne, 1995;Kaufman, Hilliker, & Daleiden, 1996;Leclerc, Proulx, & McKibben, 2005;van Dam, 2001;Young, 1997). Moreover, in the sexual offending area, researchers developed an offending process model for sexual offenders against children (e.g., Ward, Louden, Hudson, & Marshall, 1995;Ward, Polaschek, & Beech, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Over the years, studies conducted on the modus operandi of sexual offenders against children showed that these offenders exhibit some rationality in that they adopt strategies along a temporal continuum (e.g. to gain trust, to gain cooperation and to maintain victims' silence following the onset of abuse) to commit their crimes (e.g., Elliott, Browne, & Kilcoyne, 1995;Kaufman, Hilliker, & Daleiden, 1996;Leclerc, Proulx, & McKibben, 2005;van Dam, 2001;Young, 1997). Moreover, in the sexual offending area, researchers developed an offending process model for sexual offenders against children (e.g., Ward, Louden, Hudson, & Marshall, 1995;Ward, Polaschek, & Beech, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…In the company's profit report, you can find details on the net operating profit after taxes [3]. NOPAT can be calculated using the formula [14]:…”
Section: Net Operating After Tax (Nopat)mentioning
confidence: 99%
“…The cost of capital is the rate of return that must be generated by the company on project investment to maintain the market value of its shares [3]. The cost of capital (Capital Changes) can be calculated using the formula [19]:…”
Section: Capital Changes (Cc)mentioning
confidence: 99%
See 1 more Smart Citation